2004
DOI: 10.1002/14651858.cd004180.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Telephone consultation and triage: effects on health care use and patient satisfaction

Abstract: Telephone consultation appears to reduce the number of surgery contacts and out-of-hours visits by general practitioners. However, questions remain about its affect on service use and further rigorous evaluation is needed with emphasis on service use, safety, cost and patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
353
3
21

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(400 citation statements)
references
References 29 publications
14
353
3
21
Order By: Relevance
“…NTLs are also beneficial in that they reduce strain on the HCS, offer high levels of patient satisfaction, and serve as a safe, efficient, and cost-effective method of information dissemination. [19][20][21][22][23][24] Benefits can also be seen in reduced travel costs, reduced time away from school/work, and reduced childcare expenses. 17 …”
Section: Discussionmentioning
confidence: 99%
“…NTLs are also beneficial in that they reduce strain on the HCS, offer high levels of patient satisfaction, and serve as a safe, efficient, and cost-effective method of information dissemination. [19][20][21][22][23][24] Benefits can also be seen in reduced travel costs, reduced time away from school/work, and reduced childcare expenses. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Eighty-seven papers representing 83 studies were included in this review and of these eight [57][58][59][60][61][62][63][64][65] were systematic reviews. The results from the eight reviews (10 papers [57][58][59][60][61][62][63][64][65] ) are shown in Table 4.…”
Section: Systematic Reviews Includedmentioning
confidence: 99%
“…The results from the eight reviews (10 papers [57][58][59][60][61][62][63][64][65] ) are shown in Table 4. Many of the references included in the reviews overlapped.…”
Section: Systematic Reviews Includedmentioning
confidence: 99%
“…The analysis of the call reasons and the wide use of TA in 2013 led to the implementation of training courses regarding telephone triage techniques. An Italian study that investigated telephone triage quality confirmed the importance of these courses and outlined the need for improvement in this area (20).Indeed, the correct use of TA can decrease the medical workload by nearly 40% (4, 10); this result is welcomed by patients (3,8,10), and it appeared safe when it was conducted by trained operators (9).Considering the overall outcomes, our analysis outlined a lower use of outpatient and home visits than that outlined in another national study (17), highlighting to the greater number of TA outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, several countries proposed changes to primary care organization (1,2).Thus, there has been an increase in the use of telephone consultations (3)(4)(5). Telephone consultations can reduce both the emergency care visits and the number of visits overtime for general practitioners (GPs) (3)(4)(5).Moreover, the availability of telephone consultations in primary care could effectively reduce costs (6).In the literature, there is evidence that telephone consultations guarantee patient safety (7)(8)(9) and user satisfaction (3,10).…”
Section: Introductionmentioning
confidence: 99%